Esophageal Atresia with or without Tracheoesophageal Fistula (EA/TEF): Association of Different EA/TEF Subtypes with Specific Co-occurring Congenital Anomalies and Implications for Diagnostic Workup - Bogs, Thomas; Zwink, Nadine; Chonitzki, Vera; Hölscher, Alice; Boemers, Thomas M.; Münsterer, Oliver; Kurz, Ralf; Heydweiller, Andreas; Pauly, Marcus; Leutner, Andreas; Ure, Benno M.; Lacher, Martin; Deffaa, Oliver Johannes; Thiele, Holger; Bagci, Soyhan; Jenetzky, Ekkehart; Schumacher, Johannes; Reutter, Heiko (European Journal of Pediatric Surgery, 2018)
Background Esophageal atresia with or without tracheoesophageal fistula (EA/TEF) represents the most common developmental malformation of the upper digestive tract. It is classified into six subtypes according to the classification of Vogt, depending on anatomical variation of this malformation. Around 50% of the patients with EA/TEF present additional anomalies, which often influence, next to the EA/TEF subtype, the overall prognosis of EA/TEF newborns. Here, we investigated the association of the different EA/TEF subtypes with co-occurring congenital anomalies in EA/TEF patients and demonstrate their implications for postnatal diagnostic workup.Materials and Methods We investigated 333 patients of a large German multicenter study born between 1980 and 2012. After evaluation of all available clinical records, 235 patients were included in our analysis. We compared our results with existing data.Results The highest risk for co-occurring anomalies was seen in patients with most common Vogt 3b (p = 0.024), especially for additional gastrointestinal anomalies (p = 0.04). Co-occurring anomalies of the skin were significantly more common in patients with subtype Vogt 2 (p = 0.024). A significant correlation was observed for an impaired neurodevelopmental outcome and EA/TEF Vogt 3a (p = 0.041). Patients with EA/TEF showed a higher risk to present with any additional congenital anomaly compared with the general population (p < 0.001).Conclusion Our results warrant thorough clinical workup for gastrointestinal anomalies especially in patients with Vogt 3b. Moreover, it might be necessary to focus on a thorough aftercare for neurocognitive development in patients with Vogt 3a. The here presented observations need to be confirmed by future studies.
Keywords: esophageal atresia; classification of Vogt; additional congenital anomalies